Measure customer satisfaction: use the Kano Model at UUM Sultanah Bahiyah Library - Indang, Kuingatuh; Taib, Che Azlan (2017)
Customer satisfaction is defined as the number of customers, or percentage of total customers, whose reported have experience with a firm, its products, or its services with the ratings is equal or exceeds with the stated satisfaction goals.Previous literatures reviewed various models of customer satisfaction from the various perspective customer needs such as SERVQUAL, SERVPERF, application-specific integrated circuit (ASCI), Kano Model and etc.This paper emphasis on Kano Model to understanding and measures the customer’s satisfaction in UUM Sultanah Bahiyah library. In order to meet the objectives of this study, a descriptive quantitative research was chosen to get the results from the user about customer’s satisfaction at UUM Sultanah Bahiyah library with applying Kano model method.The population targeted for this study are School of Technology Management and Logistic (STML) student in UUM only for respondent to answer the questionnaire and the sample size are 100 students.The finding of this study are the first is the customers level satisfaction of customers need in terms of services and resources that librarians provided are the customers feel satisfied, second is the level of customer’s satisfaction for library service and resources if not provided properly are unsatisfied and the third is the part of the library that make customers very unsatisfied are the effectiveness of the library service dimensions and the elements of the library able to trust dimensions, then the last is the quality that practiced by the library administrators are at indifferent needs category.